Immigrants’ Characteristics and the Croatian Labour Market: an Explorative Study - Valerija Botrić (Migracijske i etničke teme, 2015)
Labour market outcomes of immigrant populations are interesting from different aspects, both as an academic question but also in terms of policy design. The potential research questions include whether immigrants face adverse prospects on local labour markets, what segment of the market do they fill and whether they contribute positively to the overall economic development of the host country. By relying mostly on the Labour Force Survey for the 1998‒2012 period, this paper aims at providing additional insight into the labour market position of immigrants in Croatia. Several indicators of the immigrant population have been compared to those of the domestic population – age, educational attainment, occupational structure and unemployment. The data indicate that immigrants in Croatia do not belong to young and highly-skilled population subgroups ‒ which are characteristics frequently associated with out-migration profiles ‒ but are instead similar to an extent to the host country population.